Systematic Literature Review Intention to Use E-Wallet - Liswanty, Ina; Muda, Iskandar; Kesuma, Sambas Ade (Ridwan Institute, 2023)
The development of the world of technology today is marked by the emergence of several types of communication technology and electronic payment systems. This payment system has revolutionized transaction methods around the world. An electronic wallet or commonly referred to as an E-Wallet is a digital payment instrument through any type of electronic media such as a computer, laptop or cell phone. Due to the ease of using e-wallets in today's daily activities, the purpose of this research is to find out what are the factors that influence people's intention to use e-wallets to carry out all types of transactions in their lives obtained through the System Literature Review method. Literature was collected from 2017-2022 and identified from 131 articles on the Emerald Insign page after several elimination stages, there were 15 articles that met the criteria that had been made. This method is used to identify, review, evaluate and interpret some of the available research on the phenomenon of interest, as well as specific related research questions. The results of this study indicate that the most common factor influencing a person's intention to use an e-wallet is perceived usefulness with the TAM theoretical model.